(untitled) (Biological Sciences - PJSIR, 2002)
From a field experiment in Cu and Mg deficient soil conducted in Muda Irrigation Scheme, Kedah , Malaysia, rice yield was found to increase significantly with the additional application of 40 kg N ha- 1 over farmers’ practice (80 kg N ha-1 . Application of Cu and Mg in the land either singly or in combination increased rice yield s and agronomic efficiency significantly. Highest yields for both the parameter s were obtained when Cu and Mg were applied in com bination. To get increased rice yield farmers could therefore, be suggested to apply Cu and Mg in combination and higher dose of N over the present rate in the fields, deficient in these two elements.